CSIG-18. ANTI-TUMOR EFFECTS OF VERTEPORFIN AND PHOTODYNAMIC THERAPY IN COMBINATION WITH STANDARD OF CARE ON PATIENT-DERIVED GBM CELL LINES. (14th November 2022) - Sudhir, Sweta; Anastasiadou, Maria; Price, Gabrielle; Hadjipanayis, Constantinos
Abstract: Glioblastoma (GBM) is the most common and aggressive primary brain tumor with a median survival of approximately 15 months. GBM tumorigenicity frequently arises from aberrant signaling transduction pathways involving receptor tyrosine kinases (RTKs), such as EGFR and PI3K. Amplification of the Epidermal Growth Factor Receptor (EGFR) gene upregulates Hippo pathway transcription factors YAP1 and TAZ, leading to tumor cell proliferation, radiation resistance, and poor survival. Verteporfin (VP), also known as Visudyne, is an FDA-approved macular degeneration photosensitizer that has photodynamic effects when combined with 489 nm of light. Additionally, VP is a small-molecule inhibitor of the YAP/TAZ/TEAD complex that has been shown to reduce tumor migration and is in phase I clinical trial as a chemotherapeutic for patients with recurrent GBM. We now investigate if VP is an effective photosensitizer for PDT in GBM and if it enhances the effects of TMZ and RT. Compared to VP alone, VP+PDT reduced the IC50 of VP treatment in GBM cells +/- EGFR amplification. Light activation of VP has a significant antitumor effect as observed with cytotoxicity in comparison to vehicle and VP treated cells (p< 0.01). Compared to control, VP, VP+PDT+TMZ, and CRT show significantly less intravasation (p< 0.01). Furthermore, Western blot analysis shows differential expression of YAP, TAZ and TEAD compared to Control and VP after treatment with VP+PDT. Differential YAP signaling is observed via IF staining in EGFR+ GBM cells treat with VP+PDT. Our research supports the use of VP as a photosensitizer in GBM cells. We found downregulation of the hippo pathway and decrease tumorigenicity of GBM cells. Application of VP-PDT treatment in combination with standard of care may be proven beneficial in GBM patients. We plan to further explore these in vitro findings in mice models and investigate other pathways including immune response with NanoString analysis.